Advances in Classical Hodgkin Lymphoma Biology: New Prognostic Factors and Outcome Prediction Using Gene Expression Signatures - Sánchez-Espiridión, Beatriz; García, Juan F.; Sánchez-Beato, Margarita (IntechOpen, 2012)
None